Effects of Lamb Waves on Ultrasonic Bounded Beam Propagation. - Plona,Thomas J. (1975)
Schlieren techniques are used to show that non-specular reflections of bounded sonic beams occur from a solid-plate/water interface when a Lamb mode of the solid plate is excited by the incident sonic beam impinging at a Lamb angle. The resulting change in the profile of the reflected beam is measured and compared to predictions based on theory. Doctoral thesis.